Competition and regulation in European retail payment systems - Kari Kemppainen (Bank of Finland, 2003)
In this study, the interaction between the competition-cooperation nexus and regulation in retail payment systems is analysed by applying the main lessons from the theory of network industries. This is justifiable on the grounds that the payment systems industry inherently has many characteristics in common with network industries.On the other hand, since the provision of payment services also has many special characteristics, the regulatory tools commonly used in many other network industries cannot be applied directly.In general, the main role of payment system regulators is to provide a level playing field for different service providers.To secure dynamic efficiency, the regulators also need to ensure adequate incentives for innovation and investment.In this respect, it is important that they do not take too restrictive an attitude towards cooperation among payment service providers.In addition to general policy analysis, the study also analyses developments in the European retail payment system field and the roles and aims of market participants.
URN:NBN:fi:bof-20140807186
Keywords: D49; G28; L98; 330; Competition policy; payment systems; retail payments; network economics